La Seine et les loisirs sportifs : le site rouennais dans l’entre-deux-guerres - Charly Machemehl (VertigO)
This case study deals with sports and leisure activities on the Seine River, and its banks, as well as in the way the inhabitants of Rouen used and transformed this space in the interwar period. By analyzing written sources - administrative files, minutes books of the city council, regional press (Normandie-Sports, Journal de Rouen, La dépêche de Rouen et deNormandie), statutes of associations -, along with semi-structured interviews, and iconographic funds, this study will show how swimming, and water sports are all important elements of urban life. The quays of the city are first and foremost dedicated to the port centered industrial and commercial developments found in the center as well as in the outskirts ; but the island « île Lacroix » houses leisure facilities, such as pontoons, boat ramps, and sunbathing and swimming areas. Indeed, most of the aquatic sports organizations, whether private clubs or community centers, are concentrated on this site, which offers the inhabitants of Rouen privileged access to the water. Secondly, the evolution of the architecture of sports facilities along the Seine illustrates the initiative of architects to adapt their plans to the constraints of the estuarine site. The building of sports centers, gymnasiums, and concert halls proved so difficult that the people of Rouen turned to the construction of big sports facilities, thus requiring the support of the public authorities, i.e. a swimming pool, or an aquatic sports stadium. In conclusion, there are numerous ways to enjoy the Seine River ; such as watching sports demonstrations, boating or canoeing - whether competitive or leisurely - or by just enjoying the view.